ESTIMATION OF RESVERATROL IN FEW NATIVE FRUITS OF NORTH-EAST INDIA - MANASHREE SHARMA; SUJOY BOSE; MANAB DEKA (International Journal of Pharma and Bio Sciences, 2015)
Resveratrol- a naturally derived stilbene, is gaining extreme popularity because of its highly appreciated multi-beneficial properties as anticancerous, antioxidant and anti-inflammatory molecule. Major dietary sources of resveratrol include grapes, berries, peanut, legumes and red wine. N.E India, rich for its wild heritage possesses many indigenous plants that have the potential to be rich source of the stilbene. Emblica officinalis, Averrhoa carambola, Elaeagnus pyriformis from native N.E India were screened for resveratrol content and HPLC based result confirm the dietary potential of resveratrol. In Phyllanthus emblica resveratrol is amounted to 43.5µg/g while in Elaeagnus pyriformis and Averrhoa carambola it is 4µg/g and 1.6µg/g respectively which is higher than many available sources such as grape and peanut. The fruits are used as alternative source of resveratrol and as neutraceuticals for many diseases by natives of India, and are easily available and low cost.